Ferroptosis: A Potential Target in Cardiovascular Disease - Leng, Yanlong; Luo, Xing; Yu, Jiaying; Jia, Haibo; Yu, Bo (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis is a new form of regulatory cell death characterized by iron-dependent and intracellular lipid peroxidation. Ferroptosis can be divided into two stages. The first stage is iron overload in the cell, which generates a large amount of reactive oxygen species through the Fenton reaction, and the second stage results from an imbalance of the intracellular antioxidant system. Excessive phospholipid hydroperoxides cannot be removed by reduction reactions, as this could destroy the cell membrane structure and interfere with mitochondrial function, eventually leading to ferroptosis of the cell. Cardiovascular diseases have gradually become the leading cause of death in modern society. The relationship between ferroptosis and the occurrence and progression of cardiovascular disease has become a research hotspot in recent years. In this review, we summarize the mechanism of ferroptosis and its specific role in cardiovascular disease.